Influenza polymerase inhibitor resistance: Assessment of the current state of the art - A report of the isirv Antiviral group - Ison, Michael G.; Hayden, Frederick G.; Hay, Alan J.; Gubareva, Larisa V.; Govorkova, Elena A.; Takashita, Emi; McKimm-Breschkin, Jennifer L. (Antiviral research, 2021)
It is more than 20 years since the neuraminidase inhibitors, oseltamivir and zanamivir were approved for the treatment and prevention of influenza. Guidelines for global surveillance and methods for evaluating resistance were established initially by the Neuraminidase Inhibitor Susceptibility Network (NISN), which merged 10 years ago with the International Society for influenza and other Respiratory Virus Diseases (isirv) to become the isirv-Antiviral Group (isirv-AVG). With the ongoing development of new influenza polymerase inhibitors and recent approval of baloxavir marboxil, the isirv-AVG held a closed meeting in August 2019 to discuss the impact of resistance to these inhibitors. Following this meeting and review of the current literature, this article is intended to summarize current knowledge regarding the clinical impact of resistance to polymerase inhibitors and approaches for surveillance and methods for laboratory evaluation of resistance, both in vitro and in animal models. We highlight limitations and gaps in current knowledge and suggest some strategies for addressing these gaps, including the need for additional clinical studies of influenza antiviral drug combinations. Lessons learned from influenza resistance monitoring may also be helpful for establishing future drug susceptibility surveillance and testing for SARS-CoV-2. •Current knowledge regarding the clinical impact of resistance to influenza polymerase inhibitors is summarized.•Current surveillance strategies for detection of variants with reduced susceptibility to polymerase inhibitors are discussed.•Methods for laboratory evaluation of resistance in vitro and in animal models, along with their limitations are presented.